The Female Hero’s Journey in Baniya’s Maharani: A Feminist-Archetypal Study - Katuwal, Saraswati (JODEM: Journal of Language and Literature, 2025)
This article, titled “The Female Hero’s Journey through the Jungle in Chandra Prakash Baniya’s Maharani: Archetypal and Feminist Readings”, examines Baniya’s historical novel Maharani (2019) through archetypal and feminist frameworks, with particular focus on the jungle as a symbolic site of female heroism. The narrative centers on Biswoprava, the Maharani of Parbat, whose journey into the Bagkhordada forest reconfigures the traditionally masculine hero’s quest into a distinctly feminine struggle for survival and resilience. Drawing on Joseph Campbell’s model of the hero’s journey and Carl Jung’s archetypes of the shadow, mother, and warrior, the study interprets Biswoprava’s endurance as an act of cultural guardianship rather than individual conquest. Complementing these archetypal insights, South Asian feminist perspectives particularly those of Chandra Talpade Mohanty, Uma Chakravarti, and Nivedita Menon situate Biswoprava’s sacrifices within broader structures of patriarchy, caste, and political erasure. The jungle functions simultaneously as a space of exile, betrayal, and conspiracy, and as a transformative arena where resilience generates renewal. By foregrounding Biswoprava’s maternal heroism and her symbolic struggle against systemic oppression, this article argues that Maharani challenges patriarchal archetypes, expands the scope of Nepali historical fiction, and contributes to South Asian feminist literary criticism. Ultimately, the novel redefines heroism through endurance, sacrifice, and communal responsibility, affirming that women’s stories are indispensable to reimagining historical memory and literary tradition.